New species of Paracerura (Collembola: Isotomidae) from Minas Gerais State, Brazil - de Mendonça, Maria Cleide; Da Silveira, Tatiana Cristina (Zootaxa, 2013)
The present paper describes Paracerura gandarela sp. nov.based on material from the Serra do Gandarela Mts., Munici-pality of Caeté, State of Minas Gerais. The new species is the sixth of the Neotropical genus Paracerura Deharveng & Oliveira, 1994 with distribution limited to Brazil. P. gandarela sp. nov. differs from other congeners especially by sensil-lary set on abdominal segments IV–V and characteristic pigmentation of the body. An identification key to species of the the genus is given.